Offloading to Improve the Battery Life of Mobile Devices - Chandra, Ranveer; Hodges, Steve; Badam, Anirudh; Huang, Jian (IEEE Pervasive Computing Magazine, 2016)
Moving the responsibility for certain computation, communication, and storage operations away from a mobile device's main processor can help save power while simultaneously increasing performance. Here, the authors present an overview of three such offloading techniques. This department is part of a special issue on energy harvesting and power management.
Spotlight